2016
DOI: 10.3390/fib4030024
|View full text |Cite
|
Sign up to set email alerts
|

Development of Touch Probing System Using a Fiber Stylus

Abstract: This paper presents a system that can be used for micro-hole measurement; the system comprises an optical fiber stylus that is 5 µm in diameter. The stylus deflects when it comes into contact with the measured surface; this deflection is measured optically. In this study, the design parameters of the optical system are determined using a ray-tracing method, and a prototype of the probing system is fabricated to verify ray-tracing simulation results; furthermore, the performance of the system is evaluated exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…The diameter of the stylus tip ranges from 1 to several 100 µm. We confirmed that the deformation of the stylus shaft with a diameter of 0.4 µm [34] and 3 µm [32] could be detected before. The measurement resolution was about 5 nm [32,34].…”
Section: Improvement Of the Optical Systemsupporting
confidence: 82%
See 2 more Smart Citations
“…The diameter of the stylus tip ranges from 1 to several 100 µm. We confirmed that the deformation of the stylus shaft with a diameter of 0.4 µm [34] and 3 µm [32] could be detected before. The measurement resolution was about 5 nm [32,34].…”
Section: Improvement Of the Optical Systemsupporting
confidence: 82%
“…We confirmed that the deformation of the stylus shaft with a diameter of 0.4 µm [34] and 3 µm [32] could be detected before. The measurement resolution was about 5 nm [32,34]. However, it is necessary to calibrate the measurement sensitivity when the stylus is replaced, because the measurement sensitivity changes depending on the diameter of the stylus shaft [32,34].…”
Section: Improvement Of the Optical Systemsupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, the hinge-typed microprobe system can perform various functions by combining MEMS and semiconductor technologies and developing a hinge mechanism. The use of the optical fiber has been proposed as a different approach [101][102][103][104][105][106][107][108][109][110][111][112][113]. Figure 5 shows some of the examples.…”
Section: Contact Probing System With Hinge Structurementioning
confidence: 99%
“…For using an optical fiber, the contact of the probe tip to the measured surface is detected by measuring the deflection of the optical fiber stem using the optical method; furthermore, high resolutions are expected for this detection. The probe deflection can be measured with high resolution; however, the reproducibility of detection is difficult to The use of the optical fiber has been proposed as a different approach [101][102][103][104][105][106][107][108][109][110][111][112][113]. Figure 5 shows some of the examples.…”
Section: Contact Probing System With Hinge Structurementioning
confidence: 99%